Synthesis and characterization of hydroxyethyl cellulose/chitosan incorporated with cellulose nanocrystal biopolymers network - Farah Hanani, Zulkifli; Khan, Sulaiman; Siti Maznah, Kabeb; Nurul Huda, Mohamed Shah (Trans Tech Publications Ltd, 2024)
Biopolymeric scaffold remains one of promising candidates in various applications, such as biomedicine, pharmaceuticals, smart packaging, and cosmetics, following its advantage of non-toxicity, safety, and sustainability in bioresources. In this study, hydroxyethyl cellulose (HEC)/ chitosan (CS) incorporated with cellulose nanocrystals (CNC) was fabricated by lyophilization technique, obtaining fine porous scaffolds structure. HEC (5 wt.%) and CS (0.1 wt.%) were prepared and blended at 50:50 ratios following the addition of CNC as nanofiller material at 1, 2 and 3 wt.%. All scaffolds were characterized by their physical, chemical, thermal, and mechanical properties via SEM, ATR-FTIR, DSC and UTM. The SEM results show HEC/CS/CNC with pore diameter ranging from 25 μm to 28 μm. The ATR-FTIR spectra indicates a broad peak of O-H stretching at 3382 cm−1 to 3397 cm−1, and C=O stretching of amide group in the range of1645cm−1 to 1653 cm−1. Mechanical testing of the samples showed increasing tensile strength with increased concentration of CNC, indicating the improved toughness of the samples. The DSC result indicates a slight decrease in glass transition and melting temperature. Overall, the HEC/CS/CNC was successfully fabricated into bioplymeric scaffolds and could be a potential substrate for biomedical application.